If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(6 + -8x) = 4x + 4 8 + (6 * -1 + -8x * -1) = 4x + 4 8 + (-6 + 8x) = 4x + 4 Combine like terms: 8 + -6 = 2 2 + 8x = 4x + 4 Reorder the terms: 2 + 8x = 4 + 4x Solving 2 + 8x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 8x + -4x = 4 + 4x + -4x Combine like terms: 8x + -4x = 4x 2 + 4x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + 4x = 4 + 0 2 + 4x = 4 Add '-2' to each side of the equation. 2 + -2 + 4x = 4 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = 4 + -2 4x = 4 + -2 Combine like terms: 4 + -2 = 2 4x = 2 Divide each side by '4'. x = 0.5 Simplifying x = 0.5
| x^2-32x-144=0 | | ln(5x+8)=0 | | xx=0 | | 2x+7+4x=-23 | | 65=17-146-46 | | 6x+5=4x+29 | | 6t+2d-t= | | 8y-4y=4 | | 7+x-4x=-20 | | 9+13-6= | | [[3]/[2]](1[3-4u]1) | | 5a^2-28a-45=-6a+3 | | 35+75+x=180 | | 10+6x-4x=-4 | | 4x^2-360000=0 | | 6u=u+15 | | Log[6]81=2 | | 15=-7x+6x+5 | | 3cos^2(x)-7cos(x)+3=0 | | 4x=1x+27 | | 55+x-40=40 | | 5x(-4)-7= | | 3m+n+m-n= | | (6/7)=(m/42) | | 72+x-7=14 | | 8x=7x+14 | | 1/5*abs(10-5x) | | 8n-9-20/7=6 | | -105=6x+5x+5 | | X2-4/2-x | | =6x+20 | | 54+x-14=60 |